Modeling RAFT gelation and grafting of polymer brushes for the production of molecularly imprinted functional particles - Oliveira, Daniela (2017)
RAFT precipitation polymerization was here used for the molecular imprinting of 5-fluorouracil (a drug used in cancer treatment) followed by grafting of polymer functional brushes in the particles surface. Materials combining high molecular recognition capabilities and stimulation triggered by changes in the surrounding environment (e.g. pH/temperature) have thus been sought. Mathematical modeling of the RAFT copolymerization of vinyl/divinyl monomers was used to describe the crosslinking process involved in the molecular imprinting step. The size of the grafted polymer functional brushes was estimated using models for the calculation of molecular weight distribution in RAFT homopolymerization. One of the goals of this study consists in the development of polymer reaction engineering tools for the design of synthesis conditions leading to tailored molecularly imprinted particles with responsive features. A first sketch of the two steps involved in the production of the MIP responsive particles is here presented. However, the need for new kinetic studies accounting for specificities of the molecular imprinting and surface extension processes (e.g. presence of template during molecular imprinting and solvent effects) is here identified. Measurements of the dynamics of gelation and brushes growth are also needed to perform model validation. Improvement on the modeling of RAFT gelation with heterogeneous conditions avoiding some simplifications and the amelioration of the numerical efficiency in the calculation of the MWD of RAFT polymers are other issues to be addressed in future works.